New vesicovaginal fistula formation in a rabbit model - Eighty M Kurniawati; Tri HS Hadi; Nur AR Widiatmoko; Widjiati Widjiati; Fedik A Rantam; Budi Santoso; Budi I Santoso; Hari Paraton; Gatut Hardianto; Azami D Azinar; Boedi Setiawan (Universitas Airlangga, 2019)
Objective: To create an animal model of vesicovaginal fistula as a modality to develop therapy.Material and Methods: This study was an preliminary experimental study to create new fistula vesicovaginal formation in a rabbit model. Six female New Zealand white rabbits of Stem Cell Research and Development Center of Universitas Airlangga were used in this study and were divided into 3 groups in which there were 2 rabbits in each group. Vesicovaginal fistula formation was performed through laparotomy surgery. After the abdomen is opened, the Nasogastric tube is inserted vaginally into the anterior vaginal wall. The incision is made on the anterior vaginal wall and the posterior wall of the bladder. The Nasogastric tube that comes out of the vagina is inserted into the bladder incision to maintain the formation of vesicovaginal fistula. Both mucosal walls are sutured and tested to determine if there is any leak. Evaluation the model of vesicovaginal fistula was carried out 3 weeks postoperatively according the group.Result: Four out of six rabbits have formed vesicovaginal fistulas, which are from groups two and three. There are no complications during the treatment period until terminationConclusion: Rabbits have the potential to become experimental animals for the vesicovaginal fistula model. The best time to release a nasogastric tube to maintain a fistula is 2 weeks.